The linguistic and economic adjustment of Soviet Jewish immigrants in the United States, 1980 to 2000 - Barry R. Chiswick; Michael Wenz (Institute for the Study of Labor (IZA), 2005)
This paper is an analysis of the English-language proficiency and labor market earnings of adult male Soviet Jewish immigrants to the United States from 1965 to 2000, using the 2000 Census of Population. Comparisons are made to similar analyses using the 1980 and 1990 Censuses. A consistent finding is that recently arrived Soviet Jewish immigrants have lower levels of English proficiency and earnings than other immigrants, other variables being the same. However, they have a steeper improvement in both proficiency and earnings with duration in the United States and the differences from the other European immigrants disappear after a few years. The Soviet Jewish immigrants have both a higher level of schooling and a larger effect of schooling on earnings than other immigrants, even other European immigrants. The lower initial English proficiency and earnings, the steeper improvement with duration and the rapid attainment of parity is consistent with the refugee nature of their migration, as distinct from being purely economic migrants. That the same pattern exists across three censuses suggests that the low English proficiency and earnings of those recently arrived in the 2000 Census data reflects a refugee assimilation process, and not a decline in the unmeasured dimensions of the earnings potential of recent cohorts of Soviet Jewish immigrants. The very high level of schooling and the larger effect of schooling on earnings among Soviet Jewish immigrants is similar to the patterns found among Jews born in the United States. Soviet Jewish immigrants appear to have made a very successful linguistic and labor market adjustment, regardless of their period of entry into the United States.
Keywords: F22; J6; J31; J24; 330; earnings; language proficiency; immigrants; Jews; Soviet Union; Juden; Russen; Mehrsprachigkeit; Einkommen; Soziale Integration; Schätzung; USA